Analgésicos Tópicos - Flores, Murilo Pereira; de Castro, Anita Perpetua Carvalho Rocha [UNESP]; Nascimento, Jedson dos Santos (Elsevier, 2012)
Background and objectives: Pain treatment involves the usage of common and opioid analgesics, nonsteroidal anti-inflammatory drugs (NSAIDs) and adjuvant analgesics. Traditionally, these drugs are administered systemically or into the neuraxis. However, when analgesics are applied through these pathways, they are associated with significant side effects, which can hinder its use. Topical administration of analgesics is an alternative. The objective of this paper is to discuss topical analgesics, the mechanisms of action and clinical efficacy. Content: This is a review paper addressing the usage of the topical local anesthetics: capsaicin, clonidine, tricyclic antidepressants, ketamine, opioids and cannabinoids, discussing mechanism of action and effectiveness. Conclusions: Topical analgesics are promising as a strategy for pain treatment, as they are associated with lower incidence of side effects. The benefit of local anesthetics, NSAID's and capsaicin is well established. However, the efficacy of clonidine, tricyclic antidepressants, ketamine, opioids and cannabinoids is still questionable. Studies have shown that the multimodal approach is an alternative, but studies are needed to confirm this hypothesis. © 2012 Elsevier Editora Ltda.
Topical Analgesics
Keywords: Administration, Topical; Analgesia; Analgesics, Opioid; Anesthetics, Local; Anti-inflammatory Agents; Antidepressive Agents, Tricyclic; Cannabinoids; Capsaicin; Ketamine; amitriptyline; analgesic agent; cannabinoid; capsaicin; clonidine; diamorphine; doxepin; EMLA; ketamine; lidocaine; local anesthetic agent; morphine; nonsteroid antiinflammatory agent; opiate; tricyclic antidepressant agent; adrenergic activity; analgesic activity; antinociception; application site burning; application site erythema; dose response; drug efficacy; drug mechanism; drug safety; hallucination; human; nausea and vomiting; neuropathic pain; nonhuman; pain; postherpetic neuralgia; respiration depression; topical treatment; Analgesics; Humans; Pain